2017
DOI: 10.1002/jctb.5411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bed compression on protein separation on gel filtration chromatography at bench and pilot scale

Abstract: BACKGROUNDPoorly packed chromatography columns are known to reduce drastically the column efficiency and produce broader peaks. Controlled bed compression has been suggested to be a useful approach for solving this problem. Here the relationship between column efficiency and resolution of protein separation are examined when preparative chromatography media were compressed using mechanical and hydrodynamic methods. Sepharose CL‐6B, an agarose based size exclusion media was examined at bench and pilot scale. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…(2) The oligosaccharides of parvalbumin may not be exposed very well due to the spatial structure of parvalbumin, which reduces the efficiency of boronate affinity ligand‐oligosaccharide interaction. (3) The agarose gel particles may also have a certain ability to separate different glycoproteins based on the principle of molecular sieve . With more precise design of boronate affinity ligands and chromatographic performance, multiple affinity performances, or in combination with other techniques such as molecular sieve and charge transfer interactions, such a significant difference in oligosaccharide content may be also used for the effective isolation of parvalbumin and other glycoproteins.…”
Section: Resultsmentioning
confidence: 99%
“…(2) The oligosaccharides of parvalbumin may not be exposed very well due to the spatial structure of parvalbumin, which reduces the efficiency of boronate affinity ligand‐oligosaccharide interaction. (3) The agarose gel particles may also have a certain ability to separate different glycoproteins based on the principle of molecular sieve . With more precise design of boronate affinity ligands and chromatographic performance, multiple affinity performances, or in combination with other techniques such as molecular sieve and charge transfer interactions, such a significant difference in oligosaccharide content may be also used for the effective isolation of parvalbumin and other glycoproteins.…”
Section: Resultsmentioning
confidence: 99%
“…There are many methods of column packing and pressure drop, besides of course column efficiency, can be one of the criteria to evaluate column packing reproducibility. For some compressible media it was demonstrated that their efficiency substantially increases when properly compressed and this finding is not limited only to particle based media but also to compressible monoliths . Last but not least, compression is also one of the main mechanisms for cell desorption from cryogels and its monitoring through a pressure drop is required to obtain proper method reproducibility.…”
Section: Pressure Drop Versus Mobile Phase Velocity Non‐linearitymentioning
confidence: 99%
“…15 During packing of compressible resins, this is often complemented by the application of a mechanical axial force on the formed bed to achieve an additional level of axial compression. 16 The correlation between packing procedure, bed homogeneity, and solute band dispersion has been the subject of many studies, 17 and involves complex interactions of packing pressure, flow ramps, slurry concentration, and the applied bed densification steps. 18 Packing procedures are often kept a secret and are described as an art rather than a science in the open literature.…”
Section: Introductionmentioning
confidence: 99%